The Estimation of Bioethanol Yield From Some Cassava Variety - M.C. Tri Atmodjo (International Conference on Engineering and Technology Development (ICETD), 2013)
In this research was examined several variety of cassava   which were , UJ-3, Kaserstaat, Caspro, and Malang 6 as the raw materials of bioethanol.  The result of the fermentation  that the bioethanol  content along 72 hours of fermentation process  showed different concentration of green energy bioethnol   between  UJ-3 ,   Kaserstaat, Malang -6 and  Caspro respectively There are  many variety of cassava which are able to use as the raw materials of Green Energy Bioethanol.    One litre of Green Energy Bioethanol usualy needs 6 kg until 7 kg  of  cassava as the raw materials.  The Total Sugar content of cassava,  will influence the amount of cassava as the raw material for bioethanol .  Sacharification process is one step of Bioethanol production will continue by fermentation process along 72 hours.                    The higest  starch content of cassava lines  got the highest  concentration green energy  bioethanol.  The lowest starch content of cassava lines  got the lowest concentration of green energy bioethanol. In this research showed that the first grade and the second grade in producing bioethanol are Kaserstaat and Caspro respectively. There are different concentration of bioethanol in each cassava lines along 72 hours of  inoculation.